Valoração e variação semânticas: um estudo sobre duas reinstanciações para o português de A late encounter with the enemy e The artificial nigger - Eduardo Assis Martins (2018)
This study examines the re-instantiation of attitudinal and engagement resources in fictional narratives translated into Brazilian Portuguese. It aims at examining the semantic variations of APPRAISAL (MARTIN; WHITE, 2005) and their role in construing the writer-translator and reader positioning in translated texts as compared to source texts. In order to carry out a semantic-discursive analysis of fictional translated texts, it adopts the discursive model of Macken-Horarik (2003) and Macken-Horarik and Isaac (2014), affiliated to the systemic functional perspective of genre of Martin and Rose (2007, 2008), the appraisal framework within this perspective, and other empirical studies that apply the APPRAISAL framework in their analysis. The research work attempts at contributing to studies of translation as re-instantiation carried out within the scope of the project Evaluation in translation of literary texts in the English/Portuguese language pair (AVATRAD). The methodology used in this study consisted of two steps. The first step involved the selection of the short stories The Artificial Nigger and A Late Encounter with the Enemy, from the collection A Good Man is Hard to Find, written by Flannery O'Connor (1992), which were translated by José Roberto O'Shea (OCONNOR, 2003) and by Leonardo Fróes (OCONNOR, 2008). The second step was divided into preliminary exploration procedures of the collection and procedures to analyze appraisal resources in the selected short stories, following the methodology proposed by Martin and White (2005) and by Macken-Horarik and Isaac (2014). These procedures consisted of the delimitation and alignment of the excerpts to be analyzed in the stages of Orientation and Resolution from each short story. After the alignment, the sentences of the texts were classified according to resources that realized engagement and attitude. Based on this classification, the realizations of attitude in the source texts and in the translated texts and their association with the narrator and the characters were analyzed, first by comparing the realizations of attitude and engagement of the source texts and translated texts, and second by taking into account the cumulative effect of the appraisal resources, according to the general evaluative orientation. The results show semantic variations in the coupling of the attitude type and mode of realization, in the coupling and commitment of graduation and in the coupling of heteroglossia. There were also variations in the description of the characters between the translated texts and the source texts, but there were no variations in the translators alignment with values expressed in translated texts. The results also show that the translated texts follow the general patterns of realization of their source texts, i.e., Orientation construing patterns which are different from the ones construed in Resolution. This helped to characterize the way the translators and readers positioning is construed and variations in this construal.